High-entropy NASICON type solid electrolyte with high conductivity
By doping a variety of metal ions in the NASICON type electrolyte, using high entropy design and solid-phase sintering method, the problems of low conductivity and poor synthesis uniformity of the existing electrolyte are solved, and high conductivity and single-phase solid solution structure are achieved electrolyte material.
Patent Information
- Application Number
- CN202411600457.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing NASICON type electrolyte has a low ion conductivity and cannot meet the needs of high specific energy batteries. At the same time, the high-entropy inorganic solid electrolyte has poor ion mixing uniformity between each metal element during material synthesis, making it difficult to achieve a single-phase solid solution structure.
Using a high-entropy design, 5 or more metal ions are doped at Zr4+ sites, and a high-entropy NASICON type solid electrolyte is synthesized by solid-phase sintering method to improve the configuration entropy and carrier concentration of the material, thereby improving the ionic conductivity.
The ionic conductivity of NASICON type electrolyte is significantly improved, the problem of poor uniformity of high-entropy inorganic electrolytes during synthesis is solved, the formation of a single-phase solid solution structure is realized, and the design space of solid electrolyte materials is expanded.
Smart Images

Figure CN119447434A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid-state batteries, and in particular relates to a high-conductivity, high-entropy NASICON-type solid electrolyte. Background Art
[0002] In recent years, traditional organic electrolyte-based batteries have been plagued by safety issues such as leakage and flammability. There is an urgent need to develop and design new electrolytes to meet social needs while promoting the development of the battery industry. Sodium metal batteries based on inorganic solid electrolytes have excellent thermal and electrochemical stability and can effectively inhibit dendrite growth, making them one of the research hotspots as the next generation of batteries. Sodium superionic conductor electrolytes (NASICON) have good mechanical properties, thermal stability, and electrochemical stability, while taking into account ion conductivity, and have gradually become one of the hot materials for studying solid electrolytes.
[0003] High entropy materials are made by doping five or more elements in (nearly) equal atomic ratios on a specific base material to form a single-phase solid solution structure. At the same time, they have a "cocktail" effect, which synergistically improves the comprehensive performance of the material. High entropy design is based on the mixed configuration entropy of the mixed system and the Gibbs free energy ΔG. mix =ΔH mix -TΔS mix , by multi-element doping to improve the mixing configuration entropy ΔS of the material system mix , which is conducive to the synthesis and thermodynamic stability of materials, especially under high temperature conditions. In the field of energy storage and power batteries, high-entropy inorganic electrolyte materials can use the differences of multiple elements to achieve multi-faceted improvements in basic materials, greatly expand the design space of electrolyte materials, and are expected to break through the performance bottleneck faced by current battery materials.
[0004] At present, the typical NASICON electrolyte Na3Zr2Si2PO 12 The ionic conductivity is only ~10 -4 S / cm, low ionic conductivity and high hardness and modulus cannot meet the needs of high specific energy batteries. Although high entropy materials can change this situation, factors such as the large number of doped elements, complex interactions between ions, and huge differences in thermodynamics and kinetics in high-temperature environments make it difficult to rationally design and controllably prepare materials. Summary of the invention
[0005] The present invention aims to provide a high-conductivity, high-entropy NASICON-type solid electrolyte The design scheme not only ensures good chemical / electrochemical stability of the material, but also improves the ionic conductivity of the NASICON electrolyte and solves the problem of poor mixing uniformity of metal element ions in high-entropy inorganic solid electrolytes during material synthesis.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] High entropy NASICON-type solid electrolyte designed according to the present invention Based on Na3Zr2Si2PO 12 Based on Zr 4+ The specific steps of synthesizing the doping of 5 or more metal ions are as follows: (1) weighing the drug: yi , Zr, Si oxides and Na2CO3 / NH4H2PO4 according to Na: The first step is to mix the chemical compositions of the raw materials in a stoichiometric ratio; (2) ball milling: all the chemicals and solvents are mixed in proportion and ball milled; (3) pre-sintering synthesis: the ball mill material is dried and pre-sintered; (4) ball milling refinement: the pre-sintered powder is mixed with the solvent and ball milled again to refine the powder; (5) constant pressure tableting: the ball milled material is tableted by cold isostatic pressing; (6) sintering densification: the electrolyte sheet is sintered to obtain a high-entropy Na-NASICON solid electrolyte. To prepare Li-type high-entropy NASICON, after completing step (4), the product is mixed with an appropriate lithium salt and a molten salt, heated to a specific temperature in a certain proportion, kept warm for a certain period of time, cooled to room temperature, and washed to remove impurities to obtain a solid electrolyte.
[0008] A high-conductivity, high-entropy NASICON-type solid electrolyte Features:
[0009] (1) The electrolyte A is an alkali metal element, specifically, A is Na or Li;
[0010] (2) Doped in A3Zr2Si2PO 12 The metal element M at the Zr site yi , which is screened based on the ionic radius, oxidation state, and valence of the element;
[0011] (3)M yi The introduction of can increase the configuration entropy of the material and reduce A + Transmission energy barrier;
[0012] (4) Through M yi The optimized combination can also increase the concentration of electrolyte carrier A and improve the conductivity.
[0013] According to some embodiments of the present invention, the Ionic radius and Close, in between.
[0014] According to some embodiments of the present invention, in step (2), the screened metal ions have a unique oxidation state Z to prevent the doped ions from undergoing redox reactions during application, thereby broadening the electrochemical window of the electrolyte.
[0015] According to some embodiments of the present invention, the valence Z includes +2, +3, +4, +5, Can be 2 + 、Cd 2+ , Ca 2+ Mg 2+ 、Zn 2+ Sc 3+ , Ga 3+ 、Al 3+ , Y 3+ 、In 3+ , Er 3+ , Gd 3+ 、Lu 3+ , Hf 4+ and Nb 5+ And other metal ions.
[0016] According to some embodiments of the present invention, in step (3), the The combination of ions should satisfy the large differences in radius and chemical valence of each ion, thereby strengthening the disorder of the material and affecting The degree of distortion and bond energy of the framework can then be used to regulate the AO bond energy, homogenize the conduction energy barrier, and increase the carrier conduction rate.
[0017] According to some embodiments of the present invention, in step (3), the total amount of doping ions is half of the Zr sites in the parent material, that is, ∑yi = 1. This can maintain a complete framework structure (composed of ZrO4 and PO4 connected at the same vertex), and on the other hand, introduce the maximum amount of doping metal ions, enhance chemical disorder, and improve the degree of lattice distortion.
[0018] According to some embodiments of the present invention, in step (4), the ratio of the doping ions should ensure that the system configuration entropy of the high entropy design is This is beneficial to the synthesis and thermodynamic stability of the material, ensuring that each doped ion successfully replaces the Zr site under high temperature conditions to form a single-phase solid solution structure.
[0019] According to some embodiments of the present invention, in step (4), the ratio of the doping ions should ensure that the carrier concentration is increased after high entropy design, so that the stoichiometric ratio of the A element is between 3.0 and 3.5, so as to improve the ionic conductivity of the electrolyte.
[0020] According to some embodiments of the present invention, when A is Li, the electrolyte can be prepared by using its corresponding Na salt through an ion exchange method.
[0021] According to some embodiments of the present invention, a high-conductivity, high-entropy NASICON-type solid electrolyte is provided, wherein the solid electrolyte is obtained by yi It is prepared by mixing the oxides of Zr and Si with Na2CO3 / NH4H2PO4 in a stoichiometric ratio and sintering at a specific temperature.
[0022] According to some embodiments of the present invention, a high-conductivity, high-entropy NASICON-type solid electrolyte is provided, wherein the solid electrolyte is obtained using the design content described in any one of claims 1-10.
[0023] Compared with the prior art, the present invention has the following gain effects:
[0024] The present invention adopts high entropy design to obtain high conductivity high entropy NASICON type solid electrolyte (A=Na / Li), by doping 5 or more metal elements to replace Zr ion sites, the configuration entropy ΔS config ≥1.5R, strengthen disorder, increase lattice distortion freedom, average ion conduction energy barrier, and greatly improve ion conductivity. At the same time, it improves the problem of poor mixing uniformity of metal element ions during the synthesis of high-entropy NASICON oxide solid electrolytes, obtains a single-phase solid solution structure, expands the design space of solid electrolyte materials, and is expected to break through the performance bottleneck faced by current battery materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0026] Figure 1 It is a process flow chart of the preparation of the high entropy NASICON solid electrolyte of the present invention;
[0027] Figure 2 is a schematic diagram of the crystal structure framework of an embodiment;
[0028] Figure 3 It is the XRD pattern of Example. DETAILED DESCRIPTION
[0029] The present invention will be described in more detail below in conjunction with the accompanying drawings and embodiments. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments, and the protection scope of the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] 1) High entropy design: Five metal elements, Zn, Mg, Sc, Hf, and Nb, were selected, each of which has a unique oxidation state and ionic radius of The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 Sc 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.5R.
[0032] 2) The oxides of Zn, Mg, Sc, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0033] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0034] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0035] Example 2
[0036] 1) High entropy design: Five metal elements, Zn, Mg, Ga, Hf, and Nb, were selected, each of which has a unique oxidation state and ionic radius of The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 Ga 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.5R.
[0037] 2) The oxides of Zn, Mg, Ga, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0038] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0039] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0040] Example 3
[0041] 1) High entropy design: Five metal elements, Zn, Mg, La, Hf, and Nb, were selected, each of which has a unique oxidation state and ionic radius of The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 La 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.5R.
[0042] 2) The oxides of Zn, Mg, La, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0043] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0044] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0045] Example 4
[0046] 1) High entropy design: Six metal elements, Zn, Mg, Ga, La, Sc, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 La 0.1 Sc 0.15 Nb 0.45 ZrSi2PO 12 , ΔS config =1.5R.
[0047] 2) The oxides of Zn, Mg, Ga, La, Sc, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0048] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0049] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0050] Example 5
[0051] 1) High entropy design: Six metal elements, Zn, Mg, Ga, La, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.3 Zn 0.1Mg 0.1 Ga 0.1 La 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.52R.
[0052] 2) The oxides of Zn, Mg, Ga, La, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0053] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0054] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0055] Example 6
[0056] 1) High entropy design: Six metal elements, Zn, Mg, Ga, Al, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 Al 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.52R.
[0057] 2) The oxides of Zn, Mg, Ga, Al, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0058] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0059] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0060] Example 7
[0061] 1) High entropy design: Six metal elements, Zn, Mg, Ga, Y, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 Y 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.52R.
[0062] 2) The oxides of Zn, Mg, Ga, Y, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0063] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0064] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0065] Example 8
[0066] 1) High entropy design: Six metal elements, Zn, Ca, Ga, La, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.3 Zn 0.1 Ca 0.1 Ga 0.1 La 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 , ΔS config =1.52R.
[0067] 2) The oxides of Zn, Ca, Ga, La, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0068] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0069] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0070] Example 9
[0071] 1) High entropy design: Six metal elements, Zn, Ca, Ga, In, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.5 Zn 0.1Ca 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 , ΔS config =1.6R.
[0072] 2) The oxides of Zn, Ca, Ga, In, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0073] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0074] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0075] Example 10
[0076] 1) High entropy design: Six metal elements, Zn, Mg, Ga, In, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.5 Zn 0.1 Mg 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 , ΔS config =1.6R.
[0077] 2) The oxides of Zn, Mg, Ga, In, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0078] 3) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 1.0 GPa.
[0079] 4) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to carry out the electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, and then maintained for 12 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a high entropy NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0080] Embodiment 11
[0081] 1) High entropy design: Six metal elements, Zn, Mg, Ga, In, Hf, and Nb, were selected, each with its unique oxidation state and ionic radius. The chemical formula is Na 3.5 Zn 0.1 Mg 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 , ΔS config =1.6R.
[0082] 2) The oxides of Zn, Mg, Ga, In, Hf, Nb, Zr and Si are weighed with Na2CO3 / NH4H2PO4 according to a stoichiometric ratio, and mixed with agate beads and ethanol by ball milling, and then a pre-sintering process is performed, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain the high entropy electrolyte powder.
[0083] 3) The obtained electrolyte powder was ball-milled with agate beads and ethanol solvent, mixed with excess LiNO3, and maintained at 350°C for 10 hours for ion exchange.
[0084] 4) Wash the ion exchanged powder to remove excess impurities and dry it to obtain Li3.5 Zn 0.1 Mg 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 .
[0085] Comparative Example 1
[0086] 1) Zr and Si oxides and Na2CO3 / NH4H2PO4 are weighed according to the stoichiometric ratio, and ball-milled with agate beads and ethanol, and then pre-sintered, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain Na3Zr2Si2PO 12 Electrolyte powder.
[0087] 2) The obtained electrolyte powder is ball-milled with agate beads and ethanol solvent, and then the powder is pressed into tablets, for example, at a tableting pressure of 500 MPa.
[0088] 3) The pressed electrolyte sheet and mother powder are placed in a ceramic crucible to perform an electrolyte sheet sintering process, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1100°C at 2°C / min, then maintained for 12 hours, then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain a NASICON electrolyte sheet for subsequent ionic conductivity testing.
[0089] Comparative Example 2
[0090] 1) Zr and Si oxides and Na2CO3 / NH4H2PO4 are weighed according to the stoichiometric ratio, and ball-milled with agate beads and ethanol, and then pre-sintered, for example, the room temperature is heated to 500°C at 9°C / min, then heated to 1000°C at 2°C / min, and then maintained for 10 hours, and then cooled to 500°C at 2°C / min, and finally cooled naturally to obtain Na3Zr2Si2PO 12 Electrolyte powder.
[0091] 2) The obtained electrolyte powder was ball-milled with agate beads and ethanol solvent, mixed with excess LiNO3, and maintained at 350°C for 10 hours for ion exchange.
[0092] 3) Wash the ion exchanged powder to remove excess impurities and dry it to obtain Li3Zr2Si2PO 12 .
[0093] Implementation Effect
[0094] The ionic conductivity of the NASICON-type oxide solid electrolytes obtained in Examples 1-11 and Comparative Examples 1-2 and the configurational entropy data of the systems are shown in Table 1:
[0095] Table 1 Related data of NASICON type oxide solid electrolyte obtained in Examples 1-11 and Comparative Examples 1-2
[0096] Example Chemical formula <![CDATA[ΔS config ]]> <![CDATA[σ i (mS / cm)]]> 1 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Sc 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.5R 6.01 2 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Ga 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.5R 5.41 3 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 La 0.2 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.5R 5.91 4 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 La 0.1 Sc 0.15 Nb 0.45 ZrSi2PO 12 ]]> 1.5R 4.16 5 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 La 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.52R 4.62 6 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 Al 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.52R 5.04 7 <![CDATA[Na 3.3 Zn 0.1 Mg 0.1 Ga 0.1 Y 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.52R 4.83 8 <![CDATA[Na 3.3 Zn 0.1 Ca 0.1 Ga 0.1 The 0.1 Hf 0.3 Nb 0.3 ZrSi2PO 12 ]]> 1.52R 4.95 9 <![CDATA[Na 3.5 Zn 0.1 Ca 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 ]]> 1.6R 5.24 10 <![CDATA[Na 3.5 Zn 0.1 Mg 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 ]]> 1.6R 5.11 11 <![CDATA[Li 3.5 Zn 0.1 Mg 0.15 Ga 0.15 In 0.15 Hf 0.15 Nb 0.3 ZrSi2PO 12 ]]> 1.6R 10.5 Comparative Example 1 <![CDATA[Na3Zr2Si2PO 12 ]]> - 0.31 2 <![CDATA[Li3Zr2Si2PO 12 ]]> - 0.54
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-conductivity, high-entropy NASICON-type solid electrolyte Features: (1) The electrolyte A is an alkali metal element, specifically, A is Na or Li; (2) Doped in A3Zr2Si2PO 12 The metal element M at the Zr site yi , which is screened based on the ionic radius, oxidation state, and valence of the element; (3)M yi The introduction of can increase the configuration entropy of the material and reduce A + Transmission energy barrier; (4) Through M yi The optimized combination can also increase the concentration of electrolyte carrier A and improve the conductivity.
2. The electrolyte according to claim 1, characterized in that Said Ionic radius and Zr 4+ Close, in between.
3. The electrolyte according to claim 1, characterized in that The screened metal ions have a unique oxidation state Z to prevent the doping ions from being (electro)oxidized / reduced during application and affecting the electrochemical window of the electrolyte.
4. The electrolyte according to claim 1, characterized in that The valence Z includes +2, +3, +4, +5, and the M yi Can be 2+ 、Cd 2+ , Ca 2+ Mg 2+ 、Zn 2+ Sc 3+ , Ga 3+ 、Al 3+ , Y 3+ 、In 3+ , Er 3+ , Gd 3+ 、Lu 3+ , Hf 4+ and Nb 5+ And other metal ions.
5. The electrolyte according to claim 1, characterized in that Said The combination of ions should satisfy the large differences in radius and chemical valence of each ion, thereby strengthening the disorder of the material and affecting The degree of distortion and bond energy of the framework can then be used to regulate the AO bond energy, homogenize the conduction energy barrier, and increase the carrier conduction rate.
6. The electrolyte according to claim 1, characterized in that The total amount of the doped ions is half of the Zr sites in the parent material, that is, ∑yi=1. This can maintain a complete framework structure (composed of ZrO4 and PO4 connected at the same vertex) on the one hand, and introduce the doped metal ion content to the maximum extent on the other hand, enhance chemical disorder, and increase the degree of lattice distortion.
7. The electrolyte according to claim 1, characterized in that The ratio of the doping ions should ensure the system configuration entropy of the high entropy design This is beneficial to the synthesis and thermodynamic stability of the material, ensuring that each doped ion successfully replaces the Zr site under high temperature conditions to form a single-phase solid solution structure.
8. The electrolyte according to claim 1, characterized in that The ratio of the doping ions should ensure that the carrier concentration is increased after the high entropy design, so that the stoichiometric number of the A element is between 3.0 and 3.5, so as to improve the ionic conductivity of the electrolyte.
9. The electrolyte according to claim 1, characterized in that When A is Li, it can be prepared by an ion exchange method using its corresponding Na salt.
10. A high-conductivity, high-entropy NASICON-type solid electrolyte, characterized in that: The solid electrolyte is prepared by yi It is prepared by mixing the oxides of Zr and Si with Na2CO3 / NH4H2PO4 in a stoichiometric ratio and sintering at a specific temperature.
11. A high-conductivity, high-entropy NASICON-type solid electrolyte, characterized in that: The solid electrolyte is obtained by adopting the design content described in any one of claims 1-10.
Citation Information
Cited By
Solid electrolyte and preparation method and application thereof
CN119812451A
Solid-state electrolyte and preparation method and application thereof
CN119812451B
Co-doped oxide solid electrolyte, preparation method thereof and sodium ion battery
CN122418015A